The load-slip characteristics of stud shear connector after hydrochloric acid corrosion. (July 2022) - Yang, Fan; Zhu, Haoyun; Qiao, Wenjing; Du, Bin
Abstract: The study of the load-slip characteristics of shear connectors is the basis for analyzing the performance of composite structures. In order to study the load-slip performance of stud shear connector after hydrochloric acid corrosion, push-out tests of six sets of stud shear connector specimens which had been corroded for 0 h, 2 h, 12 h, 24 h, 48 h and 72 h, respectively, were conducted to obtain their shear bearing capacity, load-slip curve, loading process, and failure morphology. On the basis of test verification, numerical simulation and parametric analysis were performed on 36 finite element models to study the effects of stud diameter and stud length on the load-slip performance of the stud shear connector after different corrosion time. The results show that with the increase of the corrosion time, shear bearing capacity, deformation capacity, and slip amount of stud shear connector gradually decrease. The finite element parameter analysis shows that the increase of the diameter of the stud shear connector has a significant effect on its shear bearing capacity and slip amount. When the length of the stud increases from 80 mm to 120 mm, its shear bearing capacity increases by 17.14%, and its ultimate slip amount increases by 13.11% on average. The increase in the length of the stud shear connector has a more significant effect on the shear bearing capacity. When the diameter of the stud increases from 16 mm to 22 mm, its shear bearing capacity increases by 24.76%, and its ultimate slip amount increases by 10.69% on average. The experimental results were compared with the calculation results of existing load-slip equations. Based on the comparison, the load-slip equation of the stud shear connector after strong corrosion was proposed. This study can provide a reference for the load-slip calculation of the stud shear connector after hydrochloric acid corrosion.